Improving Students’ Skill in Writing Recount Text Using Storyboard at The Ninth Grade of Junior High School - Amalia Yahya; Putri Adilah; Rusdiansyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research attempted to determine the use of Story Board in teaching writing skills in recount text in the ninth grade of SMPN 7 Palopo. This study applied a pre-experimental method. The researcher gets the score on five aspects of writing skills, content, organization, vocabulary, grammar/language use, and mechanics, by using a pre-test and post-test test. The population of this research was the ninth-grade students at SMPN 7 Palopo. There were 19 students as the sample, which is by purposive sampling. This research showed that the mean score of students writing tests in the post-test was 73.21, which is higher than the pre-test score, 60.37. Then the value of tc(tcount)= 7.56 was higher than tt(ttable)= 2.064. It means the alternative hypothesis (H1) is accepted, and (H0) is rejected. It concludes that using a storyboard to improve students' writing skills in recounting text in the ninth grade of SMPN 7 Palopo was effective.